History and Archaeology of Gadag Taluka: A Study: - (Journal of Advances and Scholarly Researches in Allied Education, 2017)
On 24th August, 1997, ‘Gadag’ emerged as a new district. In the fields of atrs,literature, culture, spiritual and industry, Gadag has its own heritage since long back.It is also a tourist place with greenery and being visited by many nature-lovers.The temples with enthralling sculptures Basadis, ancient monuments, artists, painters, musicians of international fame, reknowned poets, writers, playwrights, actors, directors, spiritual leaders, seers, scholars, social reformers, religious pivots who take people in good path – all these have enhanced the internal richness of Gadag District.